The Antimicrobial Effect of Alcoholic Extract of Olive Leaves as a Root Canal Irrigant. - Nawal A. Al-Sabawi; Nadia M. Al-Shakir; Jabbar H Kamel (University of Mosul, College of Dentistry, 2009)
Aims: The study aims to evaluate the antimicrobial effect of different concentrations of alcoholicextract of Olive Leaves solution (0.1%, 0.2%, 0.4%, 0.6%, 0.8%) in an in vitro.It also to determinesthe time required for the most effective concentration of Olive Leaves to start the effect in selectedmicroorganisms, and to evaluate the antimicrobial effect of most effective concentrations of alcoholicextract of Olive Leaves solution in an in vivo study as a root canal irrigant. Materials and Methods:The antimicrobial effect of Olive Leaves (0.1%, 0.2%, 0.4%, 0.6%, 0.8%), 2.5% sodium hypochlorite,and normal saline were determined in vitro by using broth microdilution method. The direct exposuretest was used to evaluate the time required for 0.8% of Olive Leaves to start their antimicrobial effecton the selected microorganisms. In an in vivo study, 36 uniradicular teeth with necrotic pulps werechosen. The patients were divided randomly into three groups, 12 patients for each group as in thefollowing: Group I: alcoholic extract of Olive Leaves at 0.8%. Group II: sodium hypochlorite solutionat 2.5% as a positive control. Group III: normal saline as a negative control. Bacteriological sampleswere obtained from the canal at the beginning of the first appointment; at the beginning of the secondappointment; at the end of the second appointment; at the beginning of the third appointment usingsterile wet paper point. Results: The Results showed that Olive Leaves at (0.2%, 0.4%, 0.6%, 0.8%),and sodium hypochlorite had a significant antimicrobial effect against aerobic and anaerobic bacteriarecovered from teeth with necrotic pulps. While the normal saline and 0.1% Olive Leaves had nosignificant antimicrobial effect. As for Olive Leaves exract. The best antimicrobial effect was noticedat 0.8%, which showed a significant difference from other concentrations of Olive Leaves,but nosignificant difference from that of sodium hypochlorite. The results of this test showed that 2.5%sodium hypochlorite and 0.8% Olive Leaves had immediate effect on all selected microorganisms. Theresults revealed that 0.8% alcoholic extract of Olive Leaves solution had a significant antimicrobialeffect when utilized clinically as an endodontic irrigant, which was not significantly differ from sodiumhypochlorite but significantly different from normal saline. Conclusions: Olive Leaves alcoholicextract solution at 0.8% was an effective antimicrobial agent when used as an irrigant in endodontictreatment of teeth with necrotic pulps.